Looking back on Pólya’s teaching of problem solving - Stacey, Kaye (Teaching Mathematics and Computer Science, 2022)
This article is a personal reflection on Pólya’s work on problem solving, supported by a re-reading of some of his books and viewing his film Let Us Teach Guessing. Pólya’s work has had lasting impact on the goals of school mathematics, especially in establishing solving problems (including non-routine problems) as a major goal and in establishing the elements of how to teach for problem solving. His work demonstrated the importance of choosing rich problems for students to explore, equipping them with some heuristic strategies and metacognitive awareness of the problem solving process, and promoting ’looking back’ as a way of learning from the problem solving experience. The ideas are all still influential. What has changed most is the nature of classrooms, with the subsequent appreciation of a supporting yet challenging classroom where students work collaboratively and play an active role in classroom discussion. Subject Classification: 97D50, 97A30